Preparedness for Pediatric Oral Health Promotion Among Dental Hygiene Graduates. - Evensen, D. Allison; Patrella, Megan Ciacci; Six, Margaret (Journal of Dental Hygiene, 2026)
Purpose Preventive dentistry prioritizes oral health promotion (OHP), the practice of actively teaching children and their caregivers about proper oral hygiene habits. The purpose of this study was to examine the oral health curriculum, clinical experiences, and OHP; the role of these experiences on current clinical practice and the perceptions of importance and confidence in providing pediatric care among dental hygienists recently licensed in the state of Utah. Methods Dental hygienists licensed in the state of Utah between 2022 and 2024 were invited to participate in a 20-item electronic survey about educational experiences and current clinical practices related to pediatric OHP. The survey included curriculum characteristics, the number and age of pediatric patients treated, confidence in treating age groups 1-6 and 7-12 upon graduation, the importance placed on 12 individual OHP topics, and whether previous education translated to clinical practice. Relationships among variables were assessed by statistical analyses. Results One-hundred dental hygienists accepted the invitation to participate for a 16.1% response rate. Most (86%) held a bachelor's degree. Educational experiences were significantly correlated with the importance of providing pediatric OHP in clinical practice (p<0.01). Seven out of the twelve individual topics also showed significant correlations between education received and perceived importance (p<0.03). While most (55%) felt very confident treating 7-12-year-olds, only 34% were very confident treating patients aged 1-6 years. Confidence levels were associated with the number of patients treated during dental hygiene education, with patients aged 7-12 years statistically significant (p<0.01). Conclusions Adequate educational experiences on all OHP topics as well as pediatric clinical encounters need to be ensured within dental hygiene curricula so that all graduates perceive the importance of oral health promotion when providing pediatric care and have the confidence to care for patients aged 1-12 years.